Satisfaction of mahasantri in accessing Instagram - Luthfi, Mohammad; Firmansyach , Ade Bayu (Faculty of Communications Science, Dr. Soetomo University, 2022)
Indonesia has active social media users of 68.9% or 191.4 out of 277.7 million in 2022. Instagram is the second social media platform, with active users accounting for 84.8% of the population. The use of Instagram is certainly driven by certain motives that encourage people's attitudes and beliefs to access media as needed, and Instagram can provide satisfaction according to the needs of its audience. This study aims to examine the satisfaction of the Mahasantri University of Darussalam Gontor in accessing Instagram by taking 300 samples from 1,997 populations. The data were analysed using descriptive statistics to describe the findings referring to the Expectancy Value theory as a development of the Uses and Gratification theory with two variables, namely gratifications sought (GS) and gratification obtained (GO). Then a gap test was conducted between the mean scores of the GS and GO variables to determine the satisfaction of Darussalam Gontor University students in accessing Instagram social media. The results showed that Instagram could pleasure the Mahasantri University of Darussalam Gontor in building personal relationships, filling free time, getting entertainment, fulfilling knowledge needs, and solving problems. This study answers the phenomenon of using Instagram as the second most accessed social media platform by Indonesian people, especially among teenagers. This finding positively contributes to the University of Darussalam Gontor and educational institutions' management in using Instagram as a medium of socialisation and promotion. Also, as an effort for the government to improve social media literacy for the younger generation through various creative and educational content through Instagram.